Cross-regional cultural recognition of adolescent voice emotion - Cheng, Shanshan; Li, Yue; Wang, Yingying; Zhang, Yin (Frontiers in Psychology, 2024)
BackgroundIn previous studies, an in-group advantage in emotion recognition has been demonstrated to suggest that individuals are more proficient in identifying emotions within their own culture than in other cultures. However, the existing research focuses mainly on the cross-cultural variations in vocal emotion recognition, with limited attention paid to exploring intracultural differences. Furthermore, there is little research conducted on the ability of adolescents to recognize the emotions conveyed by vocal cues in various cultural settings. To fill these research gaps, three experiments were conducted in this study to explore the differences among different regions within a culture.MethodsThe study involved three experiments. In Experiment 1, a within-subjects design of 2 (language: Mandarin vs. English) × 4 (emotion: anger vs. fear vs. happiness vs. sadness) was used to establish whether adolescents exhibit a similar in-group advantage in vocal emotion recognition with adults. As an expansion of Experiment 1, Experiment 2 incorporated the Shaoxing dialect to assess the ability of adolescents to identify the emotions in voices across different cultural regions of a nation. In Experiment 3, the regional variation was extended by substituting the Shaoxing dialect with Tibetan to explore the disparities in vocal emotion recognition among adolescents.ResultsAs indicated by the results of Experiment 1, Mandarin-speaking adolescents performed well in recognizing emotions in Mandarin compared to English. In Experiment 2, the results of Experiment 1 were replicated to reveal that Shaoxing-speaking adolescents performed better in emotion recognition of Mandarin in comparison to the Shaoxing dialect and English. As indicated by Experiment 3, both Mandarin-speaking adolescents and Tibetan-speaking adolescents possessed a higher capacity of vocal emotion recognition within their own language groups.ConclusionChinese adolescents demonstrated a stronger ability to recognize vocal emotions within their own cultural group compared to other regional cultures, an advantage that became more pronounced as the cultural differences between groups increased. These findings underscore the significance of cultural factors in adolescent emotional recognition research, indicating the directions of cross-cultural interventions.